Full Steam Ahead or Abandon Ship? An Empirical Investigation of Complete Pivot Decisions. (1st October 2019) - Wood, Matthew S.; Palich, Leslie E.; Browder, Russell E.
Abstract : New products or services often misalign with customer preferences, and sometimes these initial offerings must be abandoned and replaced. Factors influencing these "complete pivot" decisions are poorly understood. We use behavioral decision theory to develop a theoretical model of pivot decisions that tests our predictions via a conjoint analysis experiment. We find that magnitude of the miss (revenues compared to plan), length of the runway (cash available/burn rate), and attribution for the miss (reason for customer misreads) significantly influence complete pivot decisions, and we simultaneously consider interactions. Individual grit and impulsiveness also shape the effects of some attributes.